الثقافة المقاولاتية لدى الطالب الجامعي - دراسة ميدانية بجامعة محمد بوضياف المسيلة - - ذباح زينب; اشراف: بدوي سفيان (جامعة محمد بوضياف المسيلة, 2025)
يهدف هذا الموضوع الى معرفة مدى مساهمة الجامعة في نشر الثقافة المقاولاتية , حيث قمنا بدراسة الفرضية التالية = للجامعة دور في ترسيخ الثقافة المقاولاتية لدى الطالب الجامعي , اما الفرضية الفرعية الاولى لدار المقاولاتية دور في نشر الثقافة المقاولاتية لدى الطالب الجامعي ,والفرضية الفرعية الثانية يساهم المحيط الاجتماعي في تشكيل الثقافة المقاولاتية, اما الفرضية الفرعية الثالثة فكانت تساهم الوظيفة البيداغوجية في نشر الثقافة المقاولاتية , والفرضية الاخيرة لحاضنات الاعمال دور في دعم النظام المقاولاتي التي تندرج تحت سؤال الرئيسي = ما هو دور الجامعة في ترسيخ الثقافة المقاولاتية لدى الطالبة الجامعيين المقبلين على التخرج ؟ اعتمدنا على المنهج الوصفي التحليلي لدراسة وقمنا بجمع البيانات من خلال اداة الاستبيان على عينة قصدية تتكون من 50 فرد طلبة ماستر 2 قسمين علم الاجتماع وعلم النفس كلية العلوم الانسانية والاجتماعية , وقد توصلنا الى النتائج التاليةSpssبجامعة محمد بوضياف بولاية المسيلة , لمعالجة بيانات تقوم الجامعة بتقديم دورات تثقيفية للمقاولاتية وتهدف الى تزويد الطالب بالمعارف والمهارات اللازمة لدخول سوق العمل وتطوير الفكر الريادي من خلال المناهج والبحوث العلمية والمشاريع . تقدم حاضنات الاعمال الدعم والتوجيه والارشاد والمرافقة للمشاريع الناشئة من اجل جذب الاستثمار وتنمية القدرات الفكرية لكل طالب محتضن . تشير النسبة الغالبة مساهمة دار المقاولاتية في تعزيز رغبة الطالب في تأسيس مشروعه الخاص وهذا يدل على ادراك الطالب بأن ريادة الاعمال ليست مجرد خيار وظيفي بل مسار لتحقيق الذات والمساهمة في تحقيق التنمية . الكلمات المفتاحية : الثقافة المقاولاتية. الطالب. الجامعة. Studysummary: This topicaims to know the extent of the universitys contribution to spreading the entrepreneurial culture, as westudied the followinghypothesis= The university has a role in consolidating the entrepreneurial culture amonguniversitystudents, while the first sub-hypothesisisthat the social environmentcontributes to shaping the entrepreneurial culture ,while the thirdsub-hypothesiswasthat the pedagogicalfunctioncontributes to spreading the entrepreneurial culture, and the last hypothesisisthat business incubators have arole in supporting the entrepreneurial system , wwhichfallsunder the main question= Whatis the role of the university in consolidating the entrepreneurial culture amonguniversitystudentswho are about to graduate ? Werelied on the descriptive analyticalapproach to the study and collected data through the questionnaire tool on a purposivesampleconsisting of 50 individuals,Master 2 students , Departments of Sociology and Psychology, Faculty of Humanities and Social Sciences ,at Mohamed Boudiaf University ,M'silaState,toprocess the spss data and wereached the followingresults= The universityofferentrepreneurchipeducation corses thataim to providestudentswith the knowledge and skillsnecessary to enter the jopmarket and develop entrepreneurial thinkingthrough curricula ,scientificresearch ,and projects . Business incubatorsproide support ,guidance ;mentorship ,and accompaniment to emergingprojects in ordertoattractinvestment and develop the intellectualcapabilities of eachincubatedstudent . The overwhelmingpercentageindicatesthat the entrepreneurhip house contributed to enhancing the studen'sdesire to establishhisownproject .This indicates the student'sawarenessthatincreasing business is not jost a career option, but rather a path to self-realization and contributing to achievingdevelopme